Comparative analysis of the profitability of the tossa and kenaf seed cultivation at contact growers’ level in selected areas of Bangladesh - Hossain, MD. Babul; Kundu, Bishwajit (International Journal of Advanced Geosciences, 2022)
This study compared the profitability of tossa and kenaf seed cultivation based on the 2021 seed-growing season in two locations: Rangpur and Jashore using the tossa variety BJRI Tossa Pat 8 and Rangpur and Kishoreganj using the kenaf variety HC-95. Data analysis methods included descriptive statistics, break-even analysis and cost-benefit analysis. The expensive factors in growing tossa and kenaf seeds were labor costs, followed by land use, machinery, fertilizers, and seed. While the cost of labor (58.38%) and fertilizers (8.74%) were higher for tossa seed, the cost of seed (4.85%) for kenaf seed cultivation was higher as a percentage of the total cost. The highest tossa and kenaf seed yields were 722 kgha-1 and 798 kgha-1, respectively, in Jashore and Kishoreganj. Average break-even price for kenaf seed was Tk. 130 kg-1, which was less expensive than tossa seed (Tk. 181 kg-1). When compared to kenaf (341 kgha-1), average break-even quantity of tossa seed was higher (679 kgha-1). The average benefit cost ratio was found higher in the kenaf seed crop, as compared to the tossa seed crop in respect of total cost, variable cost, and cash cost. According to this finding, growing kenaf as seed crop can be profitable for farmers.